Proyecto de inversión galería de arte histórico y cultural en el distrito de Buenaventura (2013)
The offer of investment in a Gallery of Historical and cultural Art in Buenaventura's District, has as purpose to show the culture of the pacific Colombian; both to the inhabitants of the sector and to the tourists who visit the place, so that they acquire knowledge of the different aspects cultural of the region, having also the option to acquire an artistic representation of these cultural elements shown by painting, photography, sculpture and goldwork. This offer contains the particularity of not having in the place of his establishment any competition. In Buenaventura's District there is not a structure as such which has as a service the exhibition of articles and display of cultural works of art of reference of the Pacific, Being a constituent factor of absolute advantage on the market of the art. Given that there is a 95% of acceptance on the market by tourists, 98% by the inhabitants and 84% by the artisans, the investment proposal has ample opportunities to venture into the District of Buenaventura the offer of investment has wide opportunities of incursion in Buenaventura's District, given that the community and of the Pacific Region Bonaverense a benefit not only economic but also social recognition.